Psychometric Characteristics and Cultural Interpretation of LOTCA Visual Subtests Among Adults in Taiwan - Chia-Hui Hung; Ling-Jie Hung; Wan-Yi Hung; Shih-Chen Fan; Hsiao-Ping Chiu (Hong Kong Journal of Occupational Therapy, 2026)
Objectives Performance-based cognitive assessments may function differently across sociocultural contexts because language, experience, and culturally acquired representational systems influence task performance. This study examined the psychometric characteristics and culturally informed interpretation of selected Loewenstein Occupational Therapy Cognitive Assessment (LOTCA) visual subtests among adults in Taiwan. Methods A cross-sectional design was used. A total of 101 community-dwelling Taiwanese adults with intact global cognition completed selected LOTCA visual subtests. Internal consistency, content validity, exploratory factor analysis, ordinal logistic regression, and qualitative content analysis of video-recorded assessment sessions were conducted. Results Internal consistency was low at the domain level. Exploratory factor analysis identified a two-factor solution that did not reproduce the original visual perception and visuomotor construction structure. Factor 1 comprised Shape Identification (SI), Object Identification (OI), Reproduction of a Two-Dimensional Model (TM), and Puzzle Reproduction (RP), whereas Factor 2 was represented primarily by Drawing a Clock (DC). Age was associated with SI and TM, and gender was associated with TM after Bonferroni correction. Demographic influences were concentrated in SI and TM (Nagelkerke R 2 = .630 and .582, respectively). Qualitative findings identified linguistically mediated categorization, experiential familiarity, stimulus-based misidentification, and strategy-based task regulation as influences on score interpretation. Conclusions LOTCA visual subtest performance reflected interactions among perceptual demands, language, education, experience, and culturally acquired representational systems. Score variation should not be interpreted solely as evidence of cognitive limitation. Culturally informed interpretation and response-process levels may inform more accurate interpretation for visual perception performance in occupational therapy cognitive assessments.